1987
DOI: 10.5935/0305-7518.19870044
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconjunctivitis sicca in leprosy

Abstract: Summary Our studies indicate that the patient with leprosy is at risk for developing keratoconjunctivitis sicca. The cause of keratoconjunctivitis sicca in our patients suggests that the aqueous layer of the tear film may be decreased as a result of a decrease in secretion of tears from the accessory lacrimal gland of the conjunctiva although it could also be decreased due to a diseased afferent arc to the lacrimal gland or to a diseased lacrimal gland both resulting in decreased aqueous production. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…In addition, lagophthalmos could cause conjunctival goblet cell impairment, which leads to a decrease in mucin production. A study showed that human goblet cells did not have nerve endings, but their secretion could be activated with sympathetic and parasympathetic nerve stimulation ( 10 ). Patients with leprosy had a high prevalence of Meibomian gland dysfunction due to Mycobacterium leprae infiltration and infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lagophthalmos could cause conjunctival goblet cell impairment, which leads to a decrease in mucin production. A study showed that human goblet cells did not have nerve endings, but their secretion could be activated with sympathetic and parasympathetic nerve stimulation ( 10 ). Patients with leprosy had a high prevalence of Meibomian gland dysfunction due to Mycobacterium leprae infiltration and infection.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to either reduced tear secretion from the accessory lacrimal gland of the conjunctiva or autonomic denervation of the afferent arc of the lacrimal gland. [31][32][33] Madarosis was most common in LL patients. It is considered a benchmark of this form of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Intact corneal sensation is also an important factor in tear production and it is known that with a decrease in corneal sensation there is a decrease in tear secretion 4. Patients with leprosy are at risk of developing keratoconjunctivitis sicca or dry eye 5. Foreign body sensation, a major symptom in this condition can induce the patient to rub the eye excessively.…”
Section: Discussionmentioning
confidence: 99%